Analisis Karakteristik Scoby Pada Fermentasi Kombucha Air Kelapa - Lisa Yusmita; Ruri Wijayanti; Ririt Restika (CV.ITTC INDONESIA, 2026)
SCOBY (Symbiotic Colony of Bacteria and Yeast) is a colony of bacteria and yeast used in kombucha fermentation, including coconut water kombucha. Fermentation time affects the characteristics of the resulting kombucha, including SCOBY. This study aims to determine the effect of fermentation time on the characteristics of coconut water kombucha SCOBY such as nata thickness, pH, total titratable acid, cellulose content, and water content. The design used was a Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments in this study were fermentation for 1 week, 2 weeks, 3 weeks, 4 weeks, and 5 weeks. The research data were analyzed using analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. Based on the research results, the nata thickness value was between 0.09 – 0.72 cm, the pH value was between 2.55 – 4.03, the total titratable acid was 78.44 – 140.74, the cellulose content was between 0.84% ​​– 2.41% and the water content was between 70.50% – 86.67%. The fermentation time affected the nata thickness, pH, total titratable acid, cellulose content and water content of coconut water kombucha.